Comparison of medicinal preparations of Ayurveda in India and five traditional medicines in China. (10th February 2022) - Li, Xiaoli; Wu, Lei; Wu, Ruixia; Sun, Ming; Fu, Ke; Kuang, Tingting; Wang, Zhang
Abstract: Ethnopharmacological relevance: Ayurveda is the main traditional healthcare system in Indian medicine. Tibetan medicine (TM), Mongolian medicine (MM), Buddhist medicine (BM), Dai medicine (DM), and Uyghur medicine (UM) are main traditional medicines practiced in China. These are existing traditional medical systems that still play a role in disease prevention and treatment. Aim of the study: To reveal the similarities and differences of traditional medicinal preparations between Ayurveda in India and five traditional medicines in China to deepen medical exchanges and cooperation between the two countries and beyond. Methods: All preparations were extracted from statutory pharmacopoeias, ministry standards, and prescription textbooks from China and India. The information of each preparation, such as therapeutic uses, medicinal materials, and preparation forms, was recorded in Excel for statistical analysis and visual comparison. Results: A total of 645 Ayurvedic preparations, 458 TM preparations, 164 MM preparations, 616 BM preparations, 227 DM preparations, and 94 UM preparations were identified. Preparations of the six traditional medicines were mostly used for treating digestive, respiratory, and urogenital system diseases. The preparation forms of these six traditional medicines are mainly pills and powders. There are 38 shared-use medicinal materials in Ayurveda and TM preparations, 25 in Ayurveda and MM preparations, 30 in Ayurveda and BM preparations, 39 in Ayurveda and DM preparations, and 31 in Ayurveda and UM preparations. Finally, we selected one important shared-use preparation (Triphala) and 51 medicinal materials to research traditional use and modern pharmacology. Conclusions: These preparations are used by different prescribers and users of medicinal materials in different medical systems with the similarities and differences. The similarities may reflect the historical exchanges of traditional medicines between the two countries. The differences showed that traditional medicines in China have absorbed some theories, diagnoses, and treatments from Ayurveda but also retained their own ethnic and regional characteristics. Graphical abstract: Image 1